Tamãkãyã : um local de fronteiras entre matemáticas culturalmente constituídas - Melo, Éverton Melo de (2022)
This study demonstrates that knowledge of the social representation of mathematics of the Noke Koĩ indigenous community can contribute to pedagogical practice and help the school approach the mathematical manifestations present in the Campina Katukina Indigenous Land. The Noke Koĩ people are resident in a area located in the extreme western Amazon of Brazil, in the State of Acre, in the region of the river Juruá, near the city of Cruzeiro do Sul. This work emerged from my concerns during the teaching of Basic Mathematics to students of the Indigenous Higher Education course, within the scope of the Federal University of Acre, Floresta campus, an opportunity that aroused my interest in learning how this group mathematizes and later how they relate to a kind of Mathematics which at school. In this thesis, the objective was to analyze the meanings attributed to the mathematical practices socially shared by the Noke Koĩ as a process of Social Representation. This research is part of the field of qualitative research and used different data collection instruments, such as: semistructured interview, document analysis, revisiting data collected and published in Melo (2013) and the technique of free association of words. The research subjects are indigenous teachers, villagers and students from schools located within the scope of the indigenous land. Different theoretical concepts that supported the research, such as the Ethnomathematics Program, Indigenous School Education, Cultural Studies, and the Theory of Social Representations. The data reveal that this ethnic group developed a numbering system to be used in the daily life of the villages in the activities of classification, make comparison and measurement strategies. This traditional knowledge ends up being passed over to the detriment of the teaching project programmed by indigenous school education. Indigenous people build the social representation of mathematics anchored in the idea of mathematics as a school subject, that is, mathematics is understood as a curricular component. And, from this anchorage, they objectify mathematics in the view of using this knowledge in their daily practices, as knowledge that can supply the community in a dialogic relationship between indigenous and non-indigenous people.